The management of rural violence in contemporary Nigeria: the way forward - Bala, Bashir (Rural violence in contemporary Nigeria, 2023)
Modern banditry has shifted the boundaries of critical perspectives on contemporary rural violence and political economy of criminal activities. The shift manifested from its degeneration as a cultural practice that involved the stealing of cows among pastoral groups, and petty crimes, to a more sophisticated “high-tech” criminal value chain involving actors from rural and urban scapes. This sophistication engaged the employment of small arms and light weapons as well as kidnapping for ransom, gendered violence, and deployment of brutal force to earn political scores in Nigeria. The menace has also been associated with Boko Haram terrorism and insurgency, illegal gold mining, extortion of rural farmers for illegal levies, criminal operations in ungoverned spaces and the facilitation of political machinations by greedy elite in Nigeria. This chapter highlights the need to sharpen our focus on the nuances of rural violence as a manifestation of development decline, governance deficit, and crisis of security. There is also a transnational dimension in which foreign elements infiltrate the country and engage in nefarious activities. Furthermore, the devastating consequences of climate change particularly have increased influx of transhumant pastoralists into the Middle Belt and other geopolitical zones of Nigeria, where they traditionally engaged in social relations with farmers and other stakeholders in national resource allocation and management. The chapter provides constructive projections on the management of rural violence and national security in Nigeria.